Do Indonesian Male and Female Express Different Impoliteness in Social Media? a Case Study of Vadel’s Issue in Instagram - Sigalingging, Jernih; Pasaribu, Arsen Nahum; Pasaribu, Tiara Kristina (LPPPI Publishing, 2025)
This study explores the expression of impoliteness strategies by Indonesian male and female netizens in the context of the Vadel issue on Instagram. Utilizing a qualitative descriptive method, the analysis focuses on comments gathered from the platform, applying Culpeper’s (1996) framework of impoliteness strategies. The findings reveal significant gender-based differences in how impoliteness is expressed. Female commenters often employed bald-on-record and negative impoliteness strategies, reflecting a tendency toward subtle, passive-aggressive communication. In contrast, male commenters frequently utilized positive impoliteness and sarcasm, showcasing a more overtly confrontational style. Despite these differences, both genders shared a preference for direct expressions of hostility, as withhold politeness was notably absent. These results contribute to a deeper understanding of gender dynamics in digital interactions, emphasizing the diverse ways impoliteness manifests in social media discourse.